Automated People Movers and Automated Transit Systems 2020 Automated Transit for Smart Mobility - Sproule, William J. (American Society of Civil Engineers, 2020)
Selected papers from the 17th International Conference on Automated People Movers and Automated Transit Systems, held in Chicago, Illinois, June 29-July 2, 2020. Sponsored by the Transportation & Development Institute of ASCE.This collection contains 11 peer-reviewed papers on the current state and future of APMs and ATSs.Topics include: airport and other major activity centers projects; system improvements; facility planning and design; safety and security; standards; and automated train control.This proceedings will be of interest to planners, inventors, designers, suppliers, builders, owners, and operators of automated transit in all forms.
Keywords: Personal rapid transit -- Congresses.; Automated vehicles -- Congresses.; elektronické knihy; electronic books